2001
DOI: 10.1007/s004110100095
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic biomonitoring carried out in a village (Dolon) adjacent to the Semipalatinsk nuclear weapon test site

Abstract: The Semipalatinsk region (Kazakhstan Republic) has been affected by extensive radioactive contamination due to more than 450 nuclear tests of which almost 100 were exploded in the atmosphere. The present results refer to cytogenetic assessments in a study cohort of the population of Dolon, a settlement located on the NE boundary of the nuclear weapon test site, which was exposed to elevated doses of ionising radiation primarily due to the first Soviet nuclear test in 1949. Conventional cytogenetic analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…In the present study, considering entirely the studied cohort, a mean frequency of Dic + CR of 0.84 (±0.83) per 1000 cells was found. This value is very similar to other published data on Kazakhstan control subjects reported in previous studies ( Table 3 ) [ 19 , 22 , 23 , 26 , 27 , 33 ]. In particular, a mean dicentric frequency of 0.71‰ was found in a group of control subjects from Kurchatov in northeast Kazakhstan [ 19 ], while a dicentric frequency of 0.78‰ was found in a group of controls from Kokpekty in East Kazakhstan [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, considering entirely the studied cohort, a mean frequency of Dic + CR of 0.84 (±0.83) per 1000 cells was found. This value is very similar to other published data on Kazakhstan control subjects reported in previous studies ( Table 3 ) [ 19 , 22 , 23 , 26 , 27 , 33 ]. In particular, a mean dicentric frequency of 0.71‰ was found in a group of control subjects from Kurchatov in northeast Kazakhstan [ 19 ], while a dicentric frequency of 0.78‰ was found in a group of controls from Kokpekty in East Kazakhstan [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since 2018, Kazakhstan has been a member of the ARADOS (Asian Network of Biological Dosimetry) network [ 18 ], which is a platform for radiation dosimetry research among Asian countries. In addition, Kazakhstan has participated in many epidemiological studies using biological dosimetry techniques such as dicentrics, FISH translocations and physical dosimetry methods [ 19 , 20 , 21 , 22 , 23 ] as well as research on the biological effects of radiation on the human body, which further confirms the importance of research in this direction [ 24 ].…”
Section: Introductionmentioning
confidence: 97%
“…In the first four decades of nuclear testing direct individual measurements of the radiation burden to the members of the overexposed population were not carried out either by bioassay or external retrospective dosimetry assays. The studies by biological methods (Ilyinskikh et al 1997 , 1998 ; Tanaka et al 2000 , 2006 ; Testa et al 2001 ; Stephan et al 2001 ; Salomaa et al 2002 ; Chaizhunusova et al 2006 ; Takeichi et al 2006 ) or EPR or TL retrospective dosimetry (Ivannikov et al 2006 ; Stepanenko et al 2006 , 2007 ; Zhumadilov et al 2006 , 2013 ; Sholom et al 2007 ) were not made until the 1990s. Published reports in English language literature are available only after 1995.…”
Section: Scenarios Involving Incorporation Of Radionuclidesmentioning
confidence: 99%
“…Several biological dosimetry studies with the conventional cytogenetic techniques (by unstable chromosome aberrations: DC and MN assays) were performed about five decades after the beginning of the nuclear tests in 1949. These studies suggested that the current increased levels of unstable-type chromosome aberrations in the inhabitants of the most contaminated areas were mainly due to internal exposure (Tanaka et al 2000 , 2006 ; Testa et al 2001 ; Takeichi et al 2006 ) but these methods were not appropriate for long-term individual retrospective dose assessment.…”
Section: Scenarios Involving Incorporation Of Radionuclidesmentioning
confidence: 99%
“…While acknowledging the uncertainties in the method for determining radiation doses obtained decades ago, Western researchers considered a classic marker, dicentrics (one type of chromosome aberrations), suitable for detecting 'hallmarks of exposure to ionizing radiation' (Testa et al, 2001) and thus used it in the validation studies. The EU-funded project stated its objective in terms of 'verify(ing) the hypothesis of existing contamination' (Testa et al, 2001). In some of these documents, it becomes clear that at the core of the concern was the credibility of the Western scientists to their own research communities.…”
Section: Technological Innovation In the Model-and-test System: Biolomentioning
confidence: 99%